Attributes That Enhance The Positive Development Of Primary School Children: A Review - Saleh Mohamed, Saleh Sultan Almarzooqi; Kamalrudin, Massila; Al-Shami, Samer Ali Hussein; Sidek, Safiah; Akmal, Suriati (The Mattingley Publishing Co., Inc., 2020)
Positive development of primary school children (PSC) can be defined as the good changes that take place in humans as they mature from age range of primary school is roughly five to eleven years of age (between grades one and six). Currently, there is no comprehensive review to identify the attributes for positive development of primary school children. This paper provides an overview of significant attributes that affect the positive development of primary school children thorough analysis on literature studies that involve on articles study that related to primary school children‟s growth and development. There are two main significant contribution of this paper: First, there is no previous comprehensive, systematic literature review on the attributes for positive development of primary school children which is important as a reference in order to be in education system. Second, this study will provide explanations on how the significant attributes of development primary school children will lead to the effectiveness of development. The result will gives benefit in term of depth understanding or as a good reference for both academician and educationgovernment sector.